1986
DOI: 10.7326/0003-4819-105-5-649
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Regulating Hormones in Essential Hypertension

Abstract: Circulating levels of the calcium-regulating hormones, calcitonin, calcitriol, and parathyroid hormone, were analyzed in relation to plasma renin activity in 10 persons with normal blood pressure and in 51 persons with essential hypertension. Calcitriol (p less than 0.008) and parathyroid hormone (p less than 0.01) levels were elevated in hypertensives with low renin activity, whereas calcitonin levels were higher in patients with high renin activity (p less than 0.008), compared with normotensive controls and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(85 citation statements)
references
References 25 publications
6
76
3
Order By: Relevance
“…It was observed that surgically removing hyperactive parathyroids induced decreased blood pressure in SHR (Mann et al 1987, Onsgaard-Meyer et al 1994, Rybczynska et al 2005 as well as in patients with primary hyperparathyroidism (Diamond et al 1986, Resnik et al 1986, Niederle et al 1987. These findings indicated the connection between parathyroid glands and observed hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that surgically removing hyperactive parathyroids induced decreased blood pressure in SHR (Mann et al 1987, Onsgaard-Meyer et al 1994, Rybczynska et al 2005 as well as in patients with primary hyperparathyroidism (Diamond et al 1986, Resnik et al 1986, Niederle et al 1987. These findings indicated the connection between parathyroid glands and observed hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of calcium metabolism and changes in the levels of calcium-regulating hormones in essential hypertension have been described (28,570,571). However, the mechanisms that mediate these responses are unknown.…”
Section: Hypertensionmentioning
confidence: 99%
“…Resnick et al 28 have reported that in humans with low renin essential hypertension, oral administration of NaCl induces increases in blood pressure that are positively correlated with NaCl-induced increases in the plasma concentration of 1,25(OH) 2 D. In 12-week-old SHR in which blood pressure is clearly increased, the decreased levels of 1,25(OH) 2 D may be a consequence of, or a protective response to, established hypertension.…”
Section: Discussionmentioning
confidence: 99%